Association between Atrial Fibrillation and Volumetric MRI Brain Measures: Framingham Offspring Study - Piers, Ryan J. (Heart Rhythm, 2016)
BACKGROUND: The increased risk of stroke and cognitive impairment associated with atrial fibrillation (AF) is well documented. However, there is a paucity of research investigating the relations between AF and brain morphology. OBJECTIVE: Our study investigated the association between AF and brain volume measures on magnetic resonance imaging (MRI). METHODS: The study sample included stroke- and dementia-free participants who attended the Framingham Heart Study Offspring cohort 7(th) examination cycle (1999–2005) and underwent contemporaneous MRI. We examined the association between prevalent AF and brain volume measures (total cerebral volume, frontal lobe volume, temporal lobe volume, temporal horn volume, hippocampal volume, and white matter hyperintensity volume) with linear regression. We first adjusted models for age and sex, and then for vascular risk factors and APOE4. RESULTS: We studied 2144 (mean age=61.8±9.3 years; 54% women) individuals; 73 (3.4%) participants had prevalent AF at the time of MRI. In age- and sex-adjusted models, AF was inversely associated with total cerebral brain volume, frontal brain volume, and temporal brain volume. After further adjustment for vascular risk factors and APOE4, AF remained associated with frontal brain volume. CONCLUSION: After accounting for vascular risk factor burden, prevalent AF was associated with lobar indices of vascular brain aging but not with expected white matter changes.